Work-Related Psychosocial Factors and Mental Health Problems Associated with Musculoskeletal Pain in Nurses: A Cross-Sectional Study - Tiina Freimann; Mati Pääsuke; Eda Merisalu (Pain Research and Management)
Background. Musculoskeletal pain is the most common cause of incapacity among nurses. This study aimed to report the prevalence of musculoskeletal pain among hospital nurses and to explore the associations of work-related psychosocial factors and mental health problems with musculoskeletal pain. Methods. A cross-sectional survey was carried out among registered nurses at Tartu University Hospital during April and May 2011. Binary logistic regression was used to assess the associations between dependent and independent variables. Results. Analysis was based on 404 nurses (45% of the hospital’s nursing population). The overall prevalence of MSP was 70% in the past year and 64% in the past month. Lower back (57%) and neck (56%) were the body areas most commonly painful in the past year. Higher quantitative and emotional demands, work pace, low justice and respect in the workplace, influence on work organisation, and role conflicts were significantly associated with musculoskeletal pain among nurses (p<0.05). All mental health problems and most strongly somatic stress symptoms were associated with musculoskeletal pain. Conclusions. Work-related psychosocial risk factors and mental health problems, especially somatic stress symptoms, have an important impact on the occurrence of musculoskeletal pain among university hospital nurses.